Nearshore circulation on a sea breeze dominated beach during intense wind events. (1st December 2017) - Torres-Freyermuth, Alec; Puleo, Jack A.; DiCosmo, Nick; Allende-Arandía, Ma. Eugenia; Chardón-Maldonado, Patricia; López, José; Figueroa-Espinoza, Bernardo; de Alegria-Arzaburu, Amaia Ruiz; Figlus, Jens; Roberts Briggs, Tiffany M.; de la Roza, Jacobo; Candela, Julio
Abstract: A field experiment was conducted on the northern Yucatan coast from April 1 to April 12, 2014 to investigate the role of intense wind events on coastal circulation from the inner shelf to the swash zone. The study area is characterized by a micro-tidal environment, low-energy wave conditions, and a wide and shallow continental shelf. Furthermore, easterly trade winds, local breezes, and synoptic-scale events, associated with the passage of cold-fronts known as Nortes, are ubiquitous in this region. Currents were measured concurrently at different cross-shore locations during both local and synoptic-scale intense wind events to investigate the influence of different forcing mechanisms (i.e., large-scale currents, winds, tides, and waves) on the nearshore circulation. Field observations revealed that nearshore circulation across the shelf is predominantly alongshore-directed (westward) during intense winds. However, the mechanisms responsible for driving instantaneous spatial and temporal current variability depend on the weather conditions and the across-shelf location. During local strong sea breeze events ( W > 10 m s -1 from the NE) occurring during spring tide, westward circulation is controlled by the tides, wind, and waves at the inner-shelf, shallow waters, and inside the surf/swash zone, respectively. The nearshore circulation is relaxed during intense land breeze events ( W ≈ 9 m s -1 from the SE) associated with the low atmospheric pressure system that preceded a Norte event. During the Norte event ( W max ≈ 15 m s -1 from the NNW), westward circulation dominated outside the surf zone and was correlated to the Yucatan Current, whereas wave breaking forces eastward currents inside the surf/swash zone. The latter finding implies the existence of large alongshore velocity shear at the offshore edge of the surf zone during the Norte event, which enhances mixing between the surf zone and the inner shelf. These findings suggest that both sea breezes and Nortes play an important role in sediment and pollutant transport along/across the nearshore of the Yucatan shelf. Highlights: A field experiment was conducted to investigate nearshore circulation from the inner shelf to the swash zone. Currents were measured concurrently at different across-shelf location during intense wind events. Spatial and temporal variability of the different forcing mechanisms is investigated during local and synoptic scale events.